The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1152/ajprenal.00404.2012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of the impaired renal myogenic response in FHH rats

Abstract: This study examined the effect of substitution of a 2.4-megabase pair (Mbp) region of Brown Norway (BN) rat chromosome 1 (RNO1) between 258.8 and 261.2 Mbp onto the genetic background of fawn-hooded hypertensive (FHH) rats on autoregulation of renal blood flow (RBF), myogenic response of renal afferent arterioles (AF-art), K ϩ channel activity in renal vascular smooth muscle cells (VSMCs), and development of proteinuria and renal injury. FHH rats exhibited poor autoregulation of RBF, while FHH.1BN congenic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 45 publications
(47 reference statements)
0
44
0
Order By: Relevance
“…Previous studies have indicated that FHH rats develop proteinuria and renal disease as they age and that this is associated with impairment in RBF autoregulation and elevations in glomerular capillary pressure [2125]. Thus, we hypothesized that perhaps the increased susceptibility of T2DN rats to develop diabetic nephropathy might be due to introgression of a portion of the FHH genome that would alter renal hemodynamics in face of diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have indicated that FHH rats develop proteinuria and renal disease as they age and that this is associated with impairment in RBF autoregulation and elevations in glomerular capillary pressure [2125]. Thus, we hypothesized that perhaps the increased susceptibility of T2DN rats to develop diabetic nephropathy might be due to introgression of a portion of the FHH genome that would alter renal hemodynamics in face of diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…We also identified a sequence variant in the coding region of the Add3 gene in FHH rats relative to other strains (Burke et al. ). In our preliminary work, we recognized that this same variant was reported in MNS versus MHS rats, although it was originally assumed that MHS rats carried the mutant allele (Bianchi et al.…”
Section: Introductionmentioning
confidence: 90%
“…Transfer of a region of chromosome 1 containing 15 genes including the gamma‐adducin or adducin3 (Add3) gene from BN rats rescued the myogenic response of the Af‐Art, autoregulation of RBF and attenuated the development of renal injury (Burke et al. ) in an FHH.1 BN congenic strain. We also identified a sequence variant in the coding region of the Add3 gene in FHH rats relative to other strains (Burke et al.…”
Section: Introductionmentioning
confidence: 99%
“…Functional variants of Add1 have been linked to the development of hypertension in Milan hypertensive rats and humans [79] by altering the localization of plasma membrane and activity of Na+/K+-ATPase [80]. More recently, our lab has identified a genetic variant of Add3 in Fawn Hooded Hypertensive (FHH) rats that are associated with impaired myogenic response and autoregulation of renal and cerebral blood flow [81][82][83]. In addition, knockdown of Add3 expression in both renal and cerebral arteries in normal rats diminishes their myogenic responses ex vivo and enhances BK channels activity [78].…”
Section: Genes Contributing To Cerebral Autoregulationmentioning
confidence: 99%